Projeção vocal: conhecimentos e abordagens na perspectiva de professores do canto erudito - Sousa, Nadja Barbosa de (2011)
INTRODUCTION: in erudite singing the voice has to have projection to be considered functional. It is the teacher‟s role to guide the student in using favorable techniques and strategies for vocal projection during performance, using the least possible effort. However, there are controversies concerning the teaching of vocal projection, as singing teachers have different educational backgrounds and aesthetic views. PURPOSE: To analyze the perspectives and approaches regarding vocal projection, used by erudite singing teachers in Brazil. METHODS: the subjects of this study were 72 singing teachers (51 women and 21 men), working in Brazil. The participants answered, by email, an open questionnaire, composed of sample characterization data: sex, age, work places, educational background, and time of teaching experience, as well as seven questions about vocal projection in erudite singing. For purpose of this study, the answers to the two central questions were analyzed. These questions directly concerned definitions and approaches in vocal projection, according to the subjects. The answers to each question were categorized, and then statistically analyzed. In this analysis, the categories were crossed with the following variables: sex, educational background, and time of teaching experience. RESULTS: in regards to the definition of projection, the following categories were observed: body, breathing, sound production (source and filter), sound aesthetics and audibility. The categories sound production‟ and audibility‟ were mentioned more often than the rest, and the latter was mentioned by 81% of the male teachers in this study, which is statistically significant (p=0,027). With regards to the different approaches, the observed categories were: body, breathing, perception/self-perception, image and emission forms. The categories mentioned more often were breathing‟ and emission form‟. FINAL CONSIDERATIONS: to knowledge of the participating singing teachers, vocal projection was defined, predominantly, as a combination of sound production aspects and audibility. However, the reference to audibility was highlighted, as it showed statistical significance. As far as the different approaches, breathing and sound emission were emphasized as the main strategies for work and development of vocal projection in erudite singing